Angiotensin-(1-7) Central Mechanisms After ICV Infusion in Hypertensive Transgenic (mRen2)27 Rats - Kangussu, Lucas M.; Melo-Braga, Marcella Nunes; de Souza Lima, Bruna Soares; Santos, Robson A. S.; de Andrade, Hélida Monteiro; Campagnole-Santos, Maria José (Frontiers in Neuroscience, 2021)
Hypertensive rats subjected to chronic intracerebroventricular (ICV) infusion of angiotensin-(1-7) presented attenuation of arterial hypertension, improvement of baroreflex sensitivity, restoration of cardiac autonomic balance and a shift of cardiac renin-angiotensin system (RAS) balance towards Ang-(1-7)/Mas receptor. In this study, we investigated central mechanisms that could be involved in these effects, including inflammatory mediators and the expression/activity of the RAS components in hypertensive rats subjected to chronic treatment with Ang-(1-7). Furthermore, we performed a proteomic analysis to evaluate differentially regulated proteins in the hypothalamus of these animals. Sprague Dawley (SD) and transgenic (mRen2)27 hypertensive rats (TG) were subjected to 14 days of ICV infusion with Ang-(1-7) (200 ng/h) or 0.9% sterile saline (0.5 μl/h) through osmotic mini-pumps. Our results showed that treatment with Ang-(1-7) modulated inflammatory cytokines, decreasing the level of TNF-α while increasing the anti-inflammatory IL-10. Moreover, we showed a reduction in ACE activity, gene expression of the angiotensin II receptor AT1, iNOS after Ang-(1-7) treatment. Finally, our proteomic data suggested an anti-inflammatory mechanism of Ang-(1-7) toward the ROS modulators Uchl1 and Prdx1.